PERLINDUNGAN HUKUM TERHADAP PERKAWINAN TIDAK TERCATAT DALAM ADMINISTRASI KARTU KELUARGA DI INDONESIA - Umilia Zakiatuz Zahro Umilia; Bashori Alwi (LPPM STAI Muhammadiyah Probolinggo, 2026)
Marriage registration is a crucial legal mechanism to ensure legal certainty and protection for Indonesian citizens as mandated by Law Number 1 of 1974. However, in practice, unregistered marriages remain widespread due to social and economic factors, leading to legal problems particularly for wives and children concerning rights to maintenance, inheritance, and population documents. This study aims to analyze the urgency of marriage registration and evaluate the policy of including the